Rambak Product Differentiation Training and Mentoring to Improve Branding in Kandangsapi Subdistrict - Fitriyah Ulfah; Yulina Lailatul Maslukhah; Dini Pratiwi; Karina Nur Aini; Shofiyatul Laili (LPPM Universitas Timor, 2026)
To increase the potential of small businesses in Kandapi Village, Panggungrejo District, Pasuruan City. In community service activities, students strive to improve the quality and marketing of the product